Czytać między przekładami. Rzecz Czarnoleska Juliana Tuwima w języku włoskim - Wanicka, Marta (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The aim of the article is to draw attention to the value of a translation series as an interpretation tool. Its subject is the translation series consisting of five Italian translations of Julian Tuwim’s Rzecz Czarnoleska (The Czarnolas affair). The key to the analysis is the double reference to Polish Renaissance and Romanticism by allusions to Jan Kochanowski and Cyprian Kamil Norwid. The linguistic and cultural challenges have been overcome by the translators by means of different compensation strategies singled out and commented on in the article.